Assessing the digital library research output: bibliometric analysis from 2002 to 2016. Issue 4 (4th September 2018) - Ahmad, Khurshid; Jian Ming, Zheng; Rafi, Muhammad
Abstract : Purpose: The purpose of this bibliometric analysis is to quantify the prominence and impact of published literature within the field. The research has been conducted with the intent of obtaining the expansion and characteristics of the literature on digital library. Design/methodology/approach: More than 4, 206 documents found in the period of 2002-2016 were collected from the ISI Web of Science and were analyzed to explore the annual productivity, yearly citation, most cited articles, prolific authors, eminent journals of the subject, productivity of institutes and contribution of countries. These results are based on the types of documents (articles, reviews, proceedings papers, book reviews, editorial materials and book chapters). Findings: The core findings are that the most productive year of publication was 2016, and the growth of citation increased rapidly; the top source of title is electronic library. The result shows that the USA dominates in the research output, with Illinois University securing the first position; the most prolific author is Fourie I from South Africa. In the document types category, the most cited sources are research articles. Originality/value: This research is useful for the researchers interested in the field of bibliometrics as it postulates an inclusive indication of provenance in the field of library and information science.